Teliospore germination and nuclear behaviour in Urocystis hypoxyis - GANDHE, R.V. (Indian Phytopathology, 2002)
Teliospore germination in U. hypoxyis has been described in detail with reference to the nuclear division pattern. During germination, the fusion nucleus undergoes meiosis in the promycelium resulting into another division which occurs immediately and eight nuclei may be produced. U. hypoxyis develops primary sporidia at the tip of the promycelium which immediately fuse in situ or off the promycelium establishing dikaryotic condition. No secondary sporidia were developed in this species.